2005
DOI: 10.1089/jpm.2005.8.975
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Attitudinal Changes about Death and Dying as a Result of End-of-Life Care Curricula for Medical Undergraduates

Abstract: ; Reed, George W.; and Clay, Marjorie, "Detecting attitudinal changes about death and dying as a result of end-of-life care curricula for medical undergraduates" (2005 Design: A case control design (n ‫؍‬ 100) and a one group pretest-posttest design (n ‫؍‬ 98) were used to ask: (1) Are these two attitudinal measures responsive to changes induced by two undergraduate EOL curricula? (2) Do these two curricula have an additive effect (i.e., taking both yields a stronger attitudinal change than taking only one)? (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…Two studies modified the tool for the purpose of their research either by changing the terminology or the format 25 26. Five studies included original measures 16 18 19 22 23. The tables give an overview of the research articles (supplementary table 1) and they included measures ranging from more widely used and tested tools (supplementary table 2) to more recent instruments (supplementary table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies modified the tool for the purpose of their research either by changing the terminology or the format 25 26. Five studies included original measures 16 18 19 22 23. The tables give an overview of the research articles (supplementary table 1) and they included measures ranging from more widely used and tested tools (supplementary table 2) to more recent instruments (supplementary table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the self-perception of a higher level of preparedness itself may give students the willingness and confidence to remain engaged in the care of patients at the end of life as they advance in their training. Attitudinal changes, including less concern about working with dying patients, have been reported among students participating in elective end-of-life curricula 18 and self-rated knowledge and attitudes about end-oflife care may influence a physician's likelihood to refer to hospice. 19 A second potential limitation is that about 35% of graduating students did not complete the survey.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of third-year medical students, who took a 4-day orientation to end-of-life issues in which they were exposed to concepts regarding hospice and palliative care, were given a session on breaking bad news, and then visited hospice patients, revealed that the students showed significant improvements in competence and knowledge and a reduction in concern about end-of-life issues (Porter-Williamson et al, 2004). In another study, control and experimental groups of medical students were used to evaluate the responsiveness of attitudes to changes caused by an end-of-life curriculum (Schwartz et al, 2005). Those students in the end-of-life curriculum, compared with those not in this program, reported less concern about working with dying patients at the end of the course and increased their valuation of clinical criteria in thinking about a ''good death.''…”
mentioning
confidence: 99%